Sludge dewatering composite conditioner and preparation method thereof

By using composite conditioning agents composed of Lewis acid metal salt, free radical generator, surfactant, etc. in sludge treatment, the sludge dewatering efficiency and the reduction of energy consumption are achieved, and the problems of low sludge dewatering efficiency and high energy consumption in the prior art are solved.

CN119750883APending Publication Date: 2025-04-04TAIZHOU POLYTECHNIC COLLEGE

Patent Information

Application Number
CN202510041418.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing sludge conditioning agents have shortcomings in reducing the sludge moisture content and improving dehydration efficiency. Especially when dealing with high viscosity and high oily sludge, the conditioning agents are insufficient in adaptability, resulting in low dehydration efficiency and high energy consumption.

Method used

A sludge dehydration composite conditioning agent is used, which consists of Lewis acid metal salt, free radical generator, surfactant, polymeric flocculant, nanoparticle additive and pH regulator. Through the synergistic effect of chemical modification, physical flocculation and surface modification, the sludge dehydration efficiency is improved.

Benefits of technology

It significantly improves the dehydration efficiency of the sludge, reduces the moisture content of the sludge after dehydration, improves the quality of the filtrate, reduces the energy consumption of mechanical dehydration, and provides an efficient and economical sludge treatment solution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005237075320000151
    Figure BDA0005237075320000151
  • Figure BDA0005237075320000171
    Figure BDA0005237075320000171
  • Figure BDA0005237075320000191
    Figure BDA0005237075320000191
Patent Text Reader

Abstract

The invention relates to the technical field of sludge treatment, and discloses a sludge dewatering composite conditioner and a preparation method thereof.The conditioner comprises Lewis acid metal salt, a free radical generator, a surfactant, a polymeric flocculant, a nanoparticle additive and a pH regulator. The combination of polar groups on the surfaces of sludge particles and water molecules is destroyed, bound water and colloidal water are released, the flocculation performance of the particles is enhanced, meanwhile, a hydrophobic barrier is formed on the surfaces of the particles, and secondary adsorption is reduced. The conditioner disclosed by the invention is simple in preparation method and suitable for various sludge types, including municipal sludge, high-viscosity sludge and high-oil-content sludge. Experiments show that after the conditioner is used, the sludge dewatering efficiency is remarkably improved, the water content can be reduced to about 40%, and the contents of suspended solids and organic matters in filtrate are greatly reduced. The method has the advantages of high efficiency, wide adaptability and economical efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sludge treatment, in particular to a sludge dehydration composite conditioner and a preparation method thereof. Background Art

[0002] Sludge is the main by-product produced in the process of urban sewage treatment. Its water content is usually high, reaching 80% to 98%. The water in the sludge exists in complex forms, including free water, bound water and colloidal water. The mechanical dehydration process mainly relies on external force to remove free water, but the removal capacity of bound water and colloidal water is insufficient, which makes the water content of the sludge after mechanical dehydration still remain at a high level, which is difficult to meet the needs of subsequent treatment and resource utilization. Therefore, the use of chemical conditioners has become the core auxiliary measure for mechanical dehydration. The conditioners can release some water by destroying the stability and structure between sludge particles. However, the existing chemical conditioners are limited in effect and cannot achieve low-energy consumption and high-efficiency dehydration.

[0003] The widely used sludge conditioners include cationic polyacrylamide (CPAM) and inorganic salts such as aluminum salts and iron salts. As a flocculant, polyacrylamide promotes the aggregation of particles by charge neutralization, while inorganic salts reduce the electrostatic repulsion on the surface of sludge particles by destabilization. The effects of these conditioners are mainly concentrated on the physical flocculation between particles, while the release of strongly bound water in sludge involves hydrogen bonding between polar groups on the surface of sludge particles and water molecules. Existing conditioners have limited effects on these chemically bound water. Therefore, even under the action of conditioners, the moisture content of sludge after dehydration is generally higher than 60%, far from the requirements of deep dehydration.

[0004] The composition and characteristics of sludge vary significantly depending on its source. High-viscosity sludge and high-oil sludge have organic matter or grease layers on the surface of the particles, which makes them more hydrophilic and more stable, further increasing the difficulty of dehydration. Traditional conditioning agents are not adaptable enough to high-viscosity and high-oil sludge, and lack the ability to change the surface chemical properties of the particles and destroy the colloid stability, resulting in low dehydration efficiency. Especially in high-oil sludge, the grease forms a stable hydrophobic coating with the particles, making it difficult to effectively release the bound water and colloidal water between the particles. Conventional conditioning methods are inadequate in the treatment of this type of sludge.

[0005] Existing conditioning agents usually rely on a single mechanism of action, such as charge neutralization or mechanical flocculation, and fail to achieve the synergistic effect of multiple mechanisms. This limitation is obvious in the destabilization and water release of sludge particles. The flocculation effect is limited and the hydrophilicity of the particle surface is not effectively changed, resulting in low dehydration efficiency. In addition, conditioning agents are insufficient in optimizing filtrate quality. During the dehydration process, a large amount of fine particles and organic matter enter the filtrate, increasing the difficulty and cost of filtrate treatment.

[0006] At the same time, in order to make up for the inadequacy of the conditioning agent, the prior art usually requires increasing the dosage of the conditioning agent or increasing the operating pressure of the mechanical equipment. This method not only increases the processing cost, but also puts higher requirements on the performance of the mechanical equipment, further increasing energy consumption. In addition, the uneven distribution of the conditioning agent components in the sludge also limits its utilization efficiency. Some conditioning agents are wasted during the reaction process and are difficult to fully play their role. Therefore, in the field of sludge treatment, there is still a need for an efficient conditioning agent that synergizes multiple mechanisms, which can target the polar chemical bonds and structural characteristics on the surface of sludge particles, and combine physical flocculation, chemical modification, and surface modification. Function, improve dehydration efficiency, reduce energy consumption, and improve filtrate quality, thereby providing a solution for efficient sludge treatment. Summary of the invention

[0007] In view of the deficiencies in the prior art, the present invention provides a sludge dewatering composite conditioner and a preparation method thereof, in particular, a multifunctional composite conditioner designed for different types of sludge such as municipal sludge, industrial sludge, high-oil sludge, etc., which effectively improves the sludge dewatering efficiency, reduces the moisture content of the sludge after dehydration, and improves the filtrate quality through the synergistic effect of multiple mechanisms such as chemical modification, physical flocculation and surface modification, thereby providing an efficient and economical solution for sludge treatment.

[0008] To achieve the above objectives, the present invention is implemented by the following technical scheme: a sludge dehydration composite conditioner and a preparation method thereof, comprising the following components:

[0009] Lewis acid metal salts;

[0010] Free radical generators;

[0011] Surfactants;

[0012] Polymeric flocculants;

[0013] Nanoparticle additives;

[0014] pH adjuster.

[0015] Preferably, the Lewis acid metal salt is a titanate or a vanadate, specifically at least one of titanium tetrachloride, sodium metavanadate, and sodium metamolybdate.

[0016] Preferably, the free radical generator is a persulfate, specifically at least one of sodium persulfate and ammonium persulfate.

[0017] Preferably, the surfactant is an amphoteric surfactant, specifically sulfobetaine or alkylbetaine.

[0018] Preferably, the polymeric flocculant is cationic polyacrylamide.

[0019] Preferably, the nanoparticle auxiliary agent is zinc oxide or titanium dioxide nanoparticles, and the particle size thereof is 10 nm to 100 nm.

[0020] Preferably, the pH adjuster is sodium hydroxide or sodium carbonate.

[0021] A method for preparing a sludge dehydration composite conditioner comprises the following steps:

[0022] Dissolving a Lewis acid metal salt in deionized water and adjusting the pH to obtain a Lewis acid active solution;

[0023] dissolving a free radical generator in deionized water to obtain a free radical solution;

[0024] Dissolving a surfactant in deionized water to prepare a surfactant solution;

[0025] dispersing the nanoparticle auxiliary agent in deionized water by ultrasonication to obtain a nanoparticle auxiliary agent suspension;

[0026] The Lewis acid active liquid, the free radical solution, the surfactant solution, the nanoparticle auxiliary agent suspension and the flocculant are sequentially mixed according to proportions and stirred evenly to prepare a sludge dehydration composite conditioner.

[0027] Preferably, the dissolution concentration of the Lewis acid metal salt is 20% to 40%, and the pH adjustment range is 6.5 to 7.5.

[0028] Preferably, the nanoparticle auxiliary agent is dispersed by ultrasound at a power of 100W to 200W, a frequency of 20kHz to 40kHz, and an ultrasound time of 10 minutes to 20 minutes.

[0029] The present invention provides a sludge dehydration composite conditioner and a preparation method thereof, which has the following beneficial effects:

[0030] 1. The present invention adopts a technical solution combining Lewis acid metal salts with free radical generators, using the coordination effect of Lewis acid to destroy the polar bonds on the surface of sludge particles, free radical oxidation to degrade the organic structure, and release strongly bound water and colloidal water. Compared with the conditioning method in the prior art that simply relies on flocculants or inorganic salts, the present invention avoids the limitation that the treatment effect is affected by the complexity of sludge components, and solves the problem that it is difficult to remove bound water in sludge particles.

[0031] 2. The present invention introduces amphoteric surfactants and nanoparticle additives to dynamically regulate the hydrophilicity and charge distribution on the surface of sludge particles to form a hydrophobic barrier and reduce secondary water adsorption. Compared with the traditional conditioning agent that relies solely on charge neutralization or macromolecular encapsulation, it breaks through the problem of high particle water stability leading to difficulty in deep dehydration, and further improves the efficiency and thoroughness of sludge dehydration.

[0032] 3. The composite conditioner of the present invention adopts free radical oxidation and multi-scale dispersion technology, and cooperates with the step-by-step optimized mixing preparation process to achieve efficient synergy of multiple components in the conditioner. The existing technology generally has the problem of uneven components of the conditioner and large fluctuations in the use effect. The technical solution of the present invention solves this problem through the dynamic release of distributed active components, making sludge conditioning more stable and reliable.

[0033] 4. The present invention greatly reduces the mechanical resistance of sludge dehydration and significantly reduces the energy consumption of dehydration by controlling the ratio range of the conditioning agent and the process parameters. Compared with the prior art that mechanical dehydration equipment needs to rely on high pressure operation to obtain a lower moisture content, the present invention effectively alleviates the mechanical load pressure, avoids the problem of excessive energy consumption or excessive operating costs of the equipment, and provides a more economical solution for large-scale industrial promotion. DETAILED DESCRIPTION

[0034] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0035] The present invention provides a sludge dehydration composite conditioner, which can not only significantly improve the dehydration efficiency of sludge, but also effectively reduce the water content of sludge after dehydration, improve the quality of filtrate, and reduce the energy consumption of mechanical dehydration. The sludge dehydration composite conditioner provided by the present invention is mainly composed of the following four core components: Lewis acid metal salt, free radical generator, surfactant and nano additive. The following is a detailed description of each component and its specific preparation and application:

[0036] Lewis acid metal salts:

[0037] Lewis acid metal salt is one of the core components of the conditioner of the present invention, and is mainly used to change the chemical properties of the surface of sludge particles. Through the coordination of Lewis acid with carboxyl and hydroxyl groups on the surface of sludge particles, the polar binding bonds on the surface of particles are destroyed, thereby releasing bound water. Preferred Lewis acid metal salts of the present invention include titanates, vanadates and molybdates, such as titanium tetrachloride (TiCl4), sodium metavanadate (NaVO3), sodium metamolybdate (Na2MoO4), etc.

[0038] In the preparation of the conditioner, the Lewis acid metal salt is first dissolved in deionized water to form a 20% to 40% solution, and the pH value of the solution is adjusted to 6.5 to 7.5 by adding an alkaline regulator (such as NaOH) to optimize its coordination activity. The stirring time is controlled at 10 minutes to 20 minutes, and the stirring speed is 300 rpm to 500 rpm to ensure that the solution is uniform.

[0039] Free Radical Generators:

[0040] Free radical generators are used to provide strong oxidizing free radicals, such as sulfate radicals (SO4 - ), by oxidative degradation of the organic colloidal layer on the surface of the sludge particles, further weakening the stability between the particles. The preferred free radical generators of the present invention include sodium persulfate (Na2S2O8) and ammonium persulfate ((NH4)2S2O8).

[0041] During the preparation process, the free radical generator is dissolved in deionized water at a mass concentration of 5% to 10%, the dissolution temperature is maintained at 20°C to 25°C, the stirring speed is 200rpm to 400rpm, and the mixture is stirred until completely dissolved. The prepared free radical solution needs to be stored away from light to prevent the free radical generator from decomposing prematurely.

[0042] Surfactants:

[0043] The surfactant changes the physical and chemical properties of the surface of the sludge particles, reduces the surface tension between the particles, and forms a hydrophobic barrier on the surface of the particles. The preferred surfactant of the present invention is an amphoteric surfactant, such as sulfobetaine or alkylbetaine.

[0044] In the preparation of the conditioning agent, the surfactant is dissolved in warm water (30°C to 50°C) at a mass concentration of 5% to 15%, with a stirring speed of 400rpm to 600rpm and a stirring time of 5 minutes to 10 minutes until it is completely dissolved. The resulting solution is clear and transparent, with no undissolved particles, and the performance of the surfactant can be fully utilized in the subsequent sludge conditioning process.

[0045] Nano additives:

[0046] The nano-additives enhance the modification effect of the conditioner on the sludge particles through their high specific surface area and catalytic performance, and at the same time form a microstructure barrier to inhibit the sludge particles from re-adsorbing water. The preferred nano-additives of the present invention include zinc oxide (ZnO) and titanium dioxide (TiO2), and their particle size is controlled to be 10nm to 100nm.

[0047] In the preparation of the conditioning agent, the nano-additive is added to deionized water at a ratio of 1‰ to 5‰, and dispersed for 10 minutes to 20 minutes using an ultrasonic disperser (power 100W to 200W, frequency 20kHz to 40kHz) until a stable suspension is formed. Ultrasonic treatment can effectively break the agglomeration of nanoparticles and ensure their uniform distribution in the conditioning agent.

[0048] Preparation of the Conditioner Mix:

[0049] The prepared Lewis acid metal salt solution, free radical generator solution, surfactant solution and nano-additive suspension are mixed in a certain ratio of 3:1:1:1 (mass ratio). During the mixing process, the stirring speed is controlled at 400 rpm to 600 rpm, and the stirring time is 10 minutes to 15 minutes, until a uniform emulsion-like composite conditioner is formed.

[0050] The pH value of the obtained composite conditioner is controlled at 6 to 7, and it can be stably stored for 6 to 12 months at room temperature without stratification or performance change.

[0051] Sludge conditioning and dewatering process:

[0052] The sludge dehydration composite conditioner provided by the present invention is widely applicable to various types of sludge, such as municipal sludge, industrial sludge, high oil content sludge and high viscosity sludge. The following is a typical sludge conditioning and dehydration process:

[0053] Conditioner addition:

[0054] The conditioner is added to the sludge at a ratio of 5‰ to 10‰ of the wet mass of the sludge. The dosage can be adjusted according to the sludge type and treatment objectives.

[0055] Stirring reaction:

[0056] Use low-speed stirring equipment (speed 50rpm ~ 100rpm) to stir for 35 minutes to evenly distribute the conditioner on the surface of the sludge particles to enhance the reaction and flocculation effect between the particles.

[0057] Static reaction:

[0058] The standing time is 5 to 15 minutes to allow the conditioner to fully react with the sludge particles and observe the formation of sludge flocs and water separation.

[0059] Mechanical dehydration:

[0060] The conditioned sludge is sent to mechanical dehydration equipment (such as belt filter press or centrifugal dehydrator) and dehydrated at an operating pressure of 0.3MPa to 0.6MPa or a rotation speed of 1500rpm to 2000rpm. The final sludge moisture content can be reduced to 40% to 45%.

[0061] In order to further verify the performance of the sludge dehydration composite conditioner of the present invention and its applicability under different sludge types and treatment conditions, multiple groups of experimental examples and comparative experiments were conducted. The experiment compared and analyzed the differences between the conditioner of the present invention and the prior art in terms of dehydration efficiency, filtrate quality, sludge flocculation, etc. by optimizing the conditioner formula, adjusting the dosage, and testing different sludge characteristics, fully demonstrating the technical advantages and practical application effects of the present invention. The following is a detailed description of each experimental example.

[0062] Example 1: Conditioning and dewatering of municipal sludge

[0063] Conditioner Preparation:

[0064] Take 50 g of titanium tetrachloride (TiCl4) and dissolve it in deionized water to prepare a Lewis acid solution with a mass concentration of 30%;

[0065] The solution pH was adjusted to 7, and NaOH solution was added dropwise and stirred for 15 minutes at a stirring speed of 400 rpm;

[0066] Take another 15g of sodium persulfate, dissolve it in 300mL of deionized water, let it stand for 30 minutes to decompose, and set aside;

[0067] Dissolve 10 g of sulfobetaine in 50°C warm water and continue stirring until completely dissolved at a stirring speed of 500 rpm;

[0068] 2 g of nano zinc oxide was ultrasonically dispersed in 100 mL of deionized water. The ultrasonic conditions were power 150 W, frequency 25 kHz, and dispersion time 15 minutes.

[0069] Finally, the above four solutions were mixed in a ratio of 3:1:1:1 and stirred for 10 minutes to obtain a composite conditioner emulsion.

[0070] Sludge conditioning:

[0071] Take 100kg of municipal sludge (initial moisture content 78%), add 1kg of composite conditioner, and add it evenly at a ratio of 5‰;

[0072] Use a stirring device at 60 rpm for 3 minutes to ensure even distribution of the conditioner;

[0073] After standing for 10 minutes, the sludge particles gradually flocculated into agglomerates, and water separation between the particles was observed, with obvious sedimentation and stratification phenomena.

[0074] Mechanical dehydration:

[0075] The conditioned sludge was sent to the belt filter press, and the operating pressure was set to 0.4MPa. After filtration, the sludge moisture content dropped from 78% to 42.5%. The suspended matter concentration in the filtrate was controlled below 150mg / L, and there was no obvious particle deposition.

[0076] Example 2: Deep dehydration of industrial sludge

[0077] Conditioner Preparation:

[0078] Weigh 30 g of sodium metavanadate (NaVO3) and dissolve it in deionized water to make a 25% solution. Adjust the pH of the solution to 6.8.

[0079] Take 20g of sodium persulfate and dissolve it in 500mL of deionized water, and let it stand at room temperature until it is completely dissolved;

[0080] Take another 10 g of alkyl betaine, dissolve it in warm water (45°C), and stir for 5 minutes until the solution is clear;

[0081] 3 g of nano-titanium dioxide particles (TiO2, 20 nm) were dissolved in 300 mL of deionized water and dispersed by ultrasonication for 12 min at a power of 120 W;

[0082] The above solutions were mixed in a ratio of 4:2:1:1 and stirred for 8 minutes to obtain a composite conditioner.

[0083] Sludge conditioning:

[0084] Add the composite conditioner to 200kg of industrial sludge (initial moisture content 80%) at a ratio of 6‰. Use a stirring device to stir at a speed of 80rpm for 4 minutes. After standing for 15 minutes, large flocs appear in the sludge particles, colloidal water is gradually released, the volume of the sludge layer decreases, and surface moisture is obviously precipitated.

[0085] Mechanical dehydration:

[0086] The conditioned sludge is sent to the centrifugal dehydrator with the speed set at 1800rpm. After dehydration, the moisture content of the sludge is reduced to 40.8%, and the organic matter concentration in the filtrate is controlled below 200mg / L, meeting the industrial sludge discharge standard.

[0087] Example 3: Treatment of high viscosity sludge

[0088] Conditioner Preparation:

[0089] Dissolve 60 g of titanium tetrachloride (TiCl4) in 400 mL of deionized water to prepare a 35% solution.

[0090] NaOH was added to adjust the solution pH to 7.2, and the stirring time was controlled at 20 minutes and the stirring speed was 500 rpm.

[0091] Weigh 10 g of ammonium persulfate ((NH4)2S2O8) and dissolve it in 200 mL of water. After dissolution, seal and store.

[0092] Dissolve 15 g of sulfobetaine in hot water (50° C.) with a stirring speed of 600 rpm. After the solution is completely dissolved, cool it for later use.

[0093] 5 g of nano zinc oxide particles were ultrasonically dispersed in 200 mL of deionized water, the ultrasonic condition was 200 W, and the dispersion time was 18 minutes.

[0094] The above solutions were mixed in a ratio of 3:1:2:1 and stirred at low speed for 10 minutes. The conditioner was completed.

[0095] Sludge conditioning:

[0096] 100 kg of high viscosity sludge (initial water content 82%) was added with 1.5 kg of conditioning agent. The stirring speed of the stirring equipment was set to 50 rpm. After stirring for 4 minutes, the sludge began to separate. After standing for 12 minutes, the flocs further increased and the sludge viscosity decreased significantly.

[0097] Mechanical dehydration:

[0098] The conditioned sludge is sent to the filter press with the pressure set to 0.6MPa. After dehydration, the moisture content of the sludge is reduced to 43%, the filtration time is shortened by 30%, and the suspended matter content in the filtrate is stabilized below 120mg / L.

[0099] Example 4: Dewatering of High Oily Sludge

[0100] Conditioner Preparation:

[0101] Dissolve 40 g of sodium metamolybdate (Na2MoO4) in 300 mL of deionized water, add a small amount of NaOH to adjust the pH to 6.9, and stir for 15 minutes;

[0102] Dissolve 15 g of sodium persulfate in 400 mL of water and allow to stand for decomposition;

[0103] Dissolve 12 g of sulfobetaine in hot water (40°C) and stir until completely dissolved;

[0104] 2g of nano titanium dioxide (TiO2) particles were ultrasonically dispersed for 12 minutes at a power of 150W;

[0105] Mix the components in a ratio of 5:2:2:1 and stir for 5 minutes.

[0106] Sludge conditioning:

[0107] 150kg of oily sludge (water content 85%), conditioner added at a ratio of 8‰. Stirred at low speed for 3 minutes, sludge particles quickly aggregated. Set the standing time to 10 minutes, and oil-water separation was observed.

[0108] Mechanical dehydration:

[0109] The oily sludge was dehydrated by centrifugal equipment with the speed set at 2000rpm. After dehydration, the sludge moisture content dropped to 45.5% and the oil content in the filtrate dropped to below 150mg / L.

[0110] Example 5: Efficient application of composite conditioner

[0111] Conditioner Preparation:

[0112] 50g of titanium tetrachloride and 10g of sodium persulfate were selected, dissolved and stored separately. Sulfobetaine and nano zinc oxide were prepared in a conventional manner. Finally, they were mixed in a ratio of 4:1:2:1 and stirred for 12 minutes to obtain a highly uniform emulsion.

[0113] Sludge conditioning:

[0114] Sludge (200 kg, water content 78%), added at a ratio of 7‰. After stirring for 3 minutes and then standing for 15 minutes, it was observed that the sludge particles increased significantly, the bound water was released significantly, and a dense sludge layer was formed.

[0115] Mechanical dehydration:

[0116] The filter press operates at a pressure of 0.5MPa. After dehydration, the moisture content of the sludge drops to 41.5%, and the operation time is shortened by 20% compared with conventional methods.

[0117] In order to further verify the effects of the components of the present invention and their synergistic effects, multiple comparative experiments were set up. By comparing the comparative examples lacking core components or key parameter adjustments with the complete formula examples for effect analysis, the core innovations of the conditioner of the present invention and the shortcomings of the prior art can be clearly revealed. The following is a detailed setting and description of the comparative examples:

[0118] Comparative Example 1 (corresponding to Example 1): Lewis acid metal salt is not used

[0119] Conditioner Preparation:

[0120] Take 15g of sodium persulfate and dissolve it in 300mL of deionized water. Set aside after it is completely dissolved;

[0121] Dissolve 10 g of sulfobetaine in 45°C warm water, stirring at 500 rpm until completely dissolved;

[0122] 2 g of nano zinc oxide was ultrasonically dispersed in 200 mL of deionized water, with an ultrasonic power of 150 W and a dispersion time of 15 minutes;

[0123] The three solutions were mixed in a ratio of 3:1:1 and stirred for 10 minutes to obtain a conditioning agent solution. No Lewis acid metal salt component was added.

[0124] Sludge conditioning:

[0125] 1 kg of the conditioner was added to 100 kg of municipal sludge (initial moisture content 78%), the stirring speed of the stirring device was set to 60 rpm, and the stirring was performed for 3 minutes. After standing for 10 minutes, the sludge particles began to flocculate, but there was no obvious stratification phenomenon.

[0126] Mechanical dehydration:

[0127] The conditioned sludge is sent to a belt filter press for dehydration, and the operating pressure is set to 0.4MPa.

[0128] Comparative Example 2 (corresponding to Example 2): No free radical generator was used

[0129] Conditioner Preparation:

[0130] Take 30g of sodium metavanadate (NaVO3) and dissolve it in 300mL of deionized water, adjust the pH to 6.8, and adjust it drop by drop with NaOH solution, with a stirring speed of 400rpm for 15 minutes;

[0131] 10 g of sulfobetaine was dissolved in 50°C warm water with a stirring speed of 500 rpm;

[0132] 3 g of nano-titanium dioxide particles were ultrasonically dispersed in 300 mL of deionized water for 12 min;

[0133] The above three solutions were mixed in a ratio of 4:1:1 and stirred for 8 minutes to obtain a conditioner emulsion. No free radical generator component was added.

[0134] Sludge conditioning:

[0135] Take 200kg of industrial sludge (initial moisture content 80%), add 1.2kg of conditioner (dosage ratio is 6‰), stir at 80rpm, stir for 4 minutes, let stand for 15 minutes, and observe the formation of sludge flocs.

[0136] Mechanical dehydration:

[0137] The conditioned sludge is fed into a centrifugal dewatering machine, and the operating speed is set at 1800 rpm.

[0138] Comparative Example 3 (corresponding to Example 3): No surfactant was used

[0139] Conditioner Preparation:

[0140] Take 60g of titanium tetrachloride (TiCl4) and dissolve it in deionized water to make a 35% solution. Adjust the pH of the solution to 7.2 with NaOH and stir for 20 minutes at a stirring speed of 500rpm.

[0141] 10g of ammonium persulfate was dissolved in 200mL of water and allowed to stand for use. 5g of nano zinc oxide particles were ultrasonically dispersed in 200mL of deionized water at an ultrasonic power of 200W for 18 minutes.

[0142] The above solutions were mixed in a ratio of 3:1:1 and stirred at a low speed for 10 minutes to prepare a conditioner emulsion;

[0143] No sultaines or other surfactants added.

[0144] Sludge conditioning:

[0145] 100 kg of high-viscosity sludge (initial moisture content 82%) was added with 1.5 kg of conditioning agent. The stirring speed of the stirring equipment was set to 50 rpm. After stirring for 4 minutes, the mixture was allowed to stand for 12 minutes.

[0146] Mechanical dehydration:

[0147] The conditioned sludge is sent to the filter press, and the operating pressure is set to 0.6MPa

[0148] Comparative Example 4 (corresponding to Example 4): No nanoparticle additive was used

[0149] Conditioner Preparation:

[0150] 40 g of sodium metamolybdate (Na2MoO4) was dissolved in 300 mL of deionized water, the pH was adjusted to 6.9, and the stirring speed was 400 rpm for 15 minutes;

[0151] Dissolve 15 g of sodium persulfate in 400 mL of deionized water and let stand for decomposition;

[0152] Dissolve 12g of sulfobetaine in 45℃ warm water, stirring at 500rpm, and set aside after it is completely dissolved;

[0153] The solutions were mixed in a ratio of 5:2:2 and stirred for 5 minutes to prepare a conditioner emulsion;

[0154] No nano zinc oxide or other nanoparticle additives are added.

[0155] Sludge conditioning:

[0156] 150kg of oily sludge (initial moisture content 85%), conditioner is added at a ratio of 8‰, the stirring equipment is stirred at a low speed for 3 minutes, and then allowed to stand for 10 minutes.

[0157] Mechanical dehydration:

[0158] The oily sludge was dewatered by a centrifugal device, and the operating speed was set at 2000rpm.

[0159] Comparative Example 5 (corresponding to Example 5): Lewis acid metal salt concentration is reduced

[0160] Conditioner Preparation:

[0161] 25 g of titanium tetrachloride (TiCl4) was dissolved in 300 mL of deionized water to prepare a solution with a mass concentration of 15%;

[0162] The solution pH was adjusted to 7.1 with NaOH and stirred for 15 minutes at a stirring speed of 400 rpm;

[0163] Dissolve 10 g of sodium persulfate in 300 mL of water and set aside for later use;

[0164] Sulfobetaine was prepared in a conventional manner with a concentration of 10%. Nano zinc oxide was ultrasonically dispersed at a ratio of 2‰ with a power of 150W. The above four solutions were mixed at a ratio of 4:1:2:1 and stirred for 12 minutes. The Lewis acid concentration was reduced by 50% compared with that in Example 5.

[0165] Sludge conditioning:

[0166] 200kg of sludge, conditioner added at a ratio of 7‰, stirring equipment speed of 60rpm, stirring for 3 minutes, and standing for 15 minutes.

[0167] Mechanical dehydration:

[0168] The sludge was dewatered by a belt filter press, and the operating pressure was set at 0.5 MPa.

[0169] Comparative Example 6 (corresponding to Example 2): pH value was not adjusted

[0170] Conditioner Preparation:

[0171] 30 g of sodium metavanadate (NaVO3) was dissolved in 300 mL of deionized water, and the solution was used directly without pH adjustment (pH was about 5.2);

[0172] Dissolve 15 g of sodium persulfate in 500 mL of water and set aside for later use;

[0173] Dissolve 10 g of sulfobetaine in 50°C warm water and stir until completely dissolved;

[0174] 3 g of nano zinc oxide particles were dispersed by ultrasonication at 120 W for 12 min.

[0175] The above solutions were mixed in a ratio of 3:1:1:1 and stirred for 8 minutes to complete the conditioning agent.

[0176] Sludge conditioning:

[0177] 200kg of industrial sludge, add 1.2kg of conditioning agent, stir for 4 minutes, and stand for 15 minutes.

[0178] Mechanical dehydration:

[0179] Industrial sludge was treated by a centrifugal dewatering machine, and the operating speed was set at 1800 rpm.

[0180] In order to fully verify the effect of the sludge dehydration composite conditioner of the present invention and highlight its advantages over the prior art, a number of comparative experiments were designed to compare with the embodiments. By setting up comparative experiments, the effects of single component loss or parameter adjustment on dehydration performance and filtrate quality were analyzed, further proving the creativity of the conditioner of the present invention in component synergy, process optimization and application performance. The following is the comparative experimental content of the specific embodiments and comparative examples.

[0181] Experiment 1: Sludge dehydration rate comparison experiment

[0182] Subjects:

[0183] This experiment uses municipal sludge with an initial moisture content of 78% and a total sludge mass of 100 kg. Sludge is produced during the treatment of domestic sewage and has a high content of bound water and colloidal water. It needs to be dehydrated through chemical conditioning and mechanical filtration.

[0184] Experimental sample setup:

[0185] Example 1: The composite conditioner comprises titanium tetrachloride (TiCl4), sodium persulfate, sulfobetaine and nano zinc oxide.

[0186] Comparative Example 1: A conditioning agent without a Lewis acid metal salt.

[0187] Comparative Example 3: Conditioner without surfactant.

[0188] Comparative Example 4: Conditioner without nano zinc oxide.

[0189] Experimental steps:

[0190] Prepare the conditioning agent according to the conditioning agent formula in the experimental plan and stir evenly;

[0191] Each group of sludge was added with corresponding conditioning agent, and the addition ratio was 5‰ (based on the mass of wet sludge);

[0192] Use a low-speed stirring device (60 rpm) to stir for 3 minutes to ensure that the conditioner is in full contact with the sludge;

[0193] After standing for 10 minutes, the sludge enters the belt filter press. The operating pressure of the filter press is 0.4MPa;

[0194] The moisture content of the dehydrated sludge was recorded, and the residual moisture was determined by weighing. Each group of experiments was repeated 3 times and the average value was taken.

[0195] Experimental data table:

[0196] Table 1: Experimental data of the effects of different conditioners on sludge dewatering:

[0197]

[0198] Experimental summary:

[0199] After dehydration, the sludge moisture content of Example 1 is significantly lower than that of the comparative example group, reflecting the superiority of the conditioning agent of the present invention. Through the action of the Lewis acid metal salt in the conditioning agent, the polar bonds on the surface of the sludge particles are broken, and a large amount of bound water is released. In contrast, due to the lack of Lewis acid in Comparative Example 1, the polar characteristics of the sludge particles remain intact, and the bound water is insufficiently released, resulting in a high moisture content. It is difficult for a conditioning agent with a single flocculation effect to completely solve the problem of strongly bound water.

[0200] The lack of surfactant (Comparative Example 3) also showed obvious disadvantages. The introduction of surfactant reduces the surface tension of sludge particles, strengthens the formation of hydrophobic barrier, and reduces the secondary adsorption of water on the particle surface. In Comparative Example 3, the residual amount of water between particles is higher, the water decoupling between particles is insufficient, and the moisture content after dehydration is relatively high.

[0201] The synergistic effect of nanoparticle additives is also critical. The data of Comparative Example 4 shows that the dehydration efficiency of sludge is significantly reduced in the absence of nano zinc oxide. This is because nanoparticles not only provide additional active sites for chemical reactions, but also further enhance the water separation between particles through the microstructure barrier effect. In Example 1, the presence of nano additives optimizes the entire dehydration process, allowing the sludge to achieve good results even under lower mechanical pressure.

[0202] Experiment 2: Comparative experiment on flocculation of sludge particles

[0203] Subjects:

[0204] This experiment uses industrial sludge with an initial moisture content of 80% and a total sludge mass of 200 kg. The sludge comes from a chemical plant and has the characteristics of fine particles, negative charge, and high stability. Before dehydration, flocculation conditioning is required to change the particle characteristics.

[0205] Experimental sample setup:

[0206] Example 2: The composite conditioner comprises sodium metavanadate (NaVO3), sodium persulfate, sulfobetaine and nano titanium dioxide.

[0207] Comparative Example 2: The conditioner does not contain a free radical generator.

[0208] Comparative Example 6: The pH value was not adjusted by the conditioner.

[0209] Experimental steps:

[0210] Conditioner addition: Add the conditioner to the sludge sample at a ratio of 6‰ of the wet mass of the sludge to ensure that the configuration of the conditioner used in different groups meets the design requirements;

[0211] Stirring reaction: Use a stirring device to stir at 80 rpm for 4 minutes to ensure that the conditioning agent is fully dispersed and in contact with the sludge;

[0212] Standing: Let the reaction stand for 15 minutes, observe the sludge flocculation state, and record the formation of sludge flocs visible to the naked eye;

[0213] Particle size determination: Take the sludge sample after standing, measure the particle size distribution of the flocs with a laser particle size analyzer, and record the average particle size;

[0214] Floc strength determination: The sludge sample was centrifuged at low speed (1000rpm), the change in particle size of the flocs under the action of centrifugal force was measured, and the floc strength was calculated.

[0215] Experimental data record:

[0216] The average floc particle size and particle size variation of each group of samples were recorded. The experiment was repeated 3 times and the average value was taken.

[0217] Experimental data table:

[0218] Table 2: Experimental data of the effects of different conditioning agents on sludge flocculation:

[0219]

[0220] Experimental summary:

[0221] Example 2 shows a better flocculation effect, and the floc particle size is significantly larger than that of Comparative Example 2 and Comparative Example 6. The free radical generator plays an important role in this. The sulfate radicals generated by the decomposition of sodium persulfate degrade the organic colloidal layer on the surface of the sludge particles by oxidation, weakening the electrostatic repulsion between the particles, thereby promoting the particles to aggregate into larger flocs. In Comparative Example 2, the synergistic effect of free radicals is lacking, the formation of flocs is limited, and the colloidal stability between the particles is still high, resulting in a significantly smaller particle size.

[0222] Comparative Example 6, in which the pH was not adjusted, also revealed deficiencies. Under slightly acidic conditions (pH ≈ 5.2), the coordination activity of the Lewis acid metal salt decreased, the vanadate could not effectively bind to the polar groups on the sludge surface, and the surface modification of the particles was inhibited, affecting the flocculation process. At the same time, the decomposition rate of the free radical generator in a slightly acidic environment was unstable, resulting in insufficient overall activity of the conditioner.

[0223] In the experiment, the floc particle size of Example 2 maintained a high stability under the action of centrifugal force, and the particle size change was only 14.2%. This phenomenon shows that the conditioning agent improves the mechanical strength and structural integrity of the floc by introducing surfactants and nanoparticle additives. However, the floc particle size of Comparative Examples 2 and 6 decreased significantly under the action of centrifugal force, indicating that their floc structure is relatively loose and lacks stability. This further proves the advantages of the conditioning agent of Example 2 in particle surface reaction and flocculation enhancement.

[0224] Experiment 3: Filtrate quality comparison experiment

[0225] Subjects:

[0226] This experiment uses high-viscosity sludge with an initial moisture content of 82% and a total sludge mass of 100 kg. The sludge comes from the wastewater treatment system of a food processing plant, has a high content of colloidal organic matter and flocculation stability, and the suspended matter concentration in the filtrate is high.

[0227] Experimental sample setup:

[0228] Example 3: The conditioning agent consists of titanium tetrachloride (TiCl4), ammonium persulfate, sulfobetaine and nano zinc oxide.

[0229] Comparative Example 1: The conditioner does not contain a Lewis acid metal salt.

[0230] Comparative Example 4: The conditioner does not contain nano zinc oxide.

[0231] Experimental steps:

[0232] Conditioning agent preparation: Prepare the corresponding reagents according to the formula of each group of conditioning agents, ensure that they are fully dissolved and stirred evenly;

[0233] Addition of conditioning agent: Each group of conditioning agent is added to the high viscosity sludge sample at a ratio of 1.5‰ of the wet mass of the sludge;

[0234] Stirring reaction: Stir the sludge and conditioning agent in a low-speed stirring device at a speed of 50 rpm for 4 minutes;

[0235] Standing reaction: Standing for 12 minutes, observing the separation of sludge particles and the transparency of the upper filtrate;

[0236] Mechanical dewatering: The conditioned sludge sample was fed into a filter press with the operating pressure set at 0.6 MPa, and the filtrate was collected for analysis;

[0237] Filtrate quality determination: Take a filtrate sample, filter it with filter paper, and determine the mass of the residue on the filter paper. The suspended matter concentration (mg / L) is used to characterize the filtrate quality.

[0238] Experimental data record:

[0239] The suspended matter concentration of each group of filtrates was recorded, and the experiment was repeated 3 times to take the average value.

[0240] Experimental data table:

[0241] Table 3: Experimental data on the effects of different conditioning agents on the concentration of suspended solids in the filtrate:

[0242]

[0243] Experimental summary:

[0244] Example 3 shows excellent filtrate quality, and the suspended matter concentration is significantly lower than that of the comparative example group. This is due to the synergistic effect of the Lewis acid metal salt and the free radical generator in the conditioner. Titanium tetrachloride coordinates with the carboxyl and hydroxyl groups on the surface of the sludge particles, destroying their polar structure, loosening the colloidal water and bound water between the particles, and the released fine particles are captured by the flocculant instead of entering the filtrate. In the absence of Lewis acid metal salt in comparative example 1, the polar bound water on the surface of the sludge particles cannot be fully released, and the fine particles are more likely to remain in the filtrate, resulting in a higher suspended matter concentration in the filtrate.

[0245] The introduction of nanoparticle additives obviously enhances the overall performance of the conditioner. In Example 3, nano zinc oxide not only accelerates the aggregation of sludge particles by catalyzing surface reactions, but also reduces the risk of redispersion of particles in the filtrate through the microstructure barrier effect. In Comparative Example 4, the lack of nano zinc oxide leads to an improvement in the dehydration effect of sludge, but the concentration of suspended matter in the filtrate is still high. This shows that nano additives play an important role in improving the quality of the filtrate.

[0246] In addition, the oxidative action of the free radical generator plays a key role in the whole process. In Example 3, the sulfate radicals released by ammonium persulfate not only degraded the organic colloidal components in the sludge, but also further destroyed the stability of the particles, providing more effective opportunities for the surfactant and flocculant to act. The data of Comparative Example 1 verified that without this process, the depth of action of the sludge conditioner was obviously insufficient, which ultimately led to a higher level of pollutants in the filtrate. This series of mechanisms work together to make the filtrate quality of Example 3 better than other groups, especially in terms of suspended matter concentration control, achieving a more ideal effect.

[0247] Experiment 4: Comparative experiment on dehydration effect of high oil content sludge

[0248] Subjects:

[0249] This experiment uses high-oil sludge with an initial moisture content of 85% and a total sludge mass of 150kg, which comes from a petrochemical wastewater treatment station. The sludge contains a large amount of oily substances, has a strong hydrophobic surface, and has high particle stability, so it is difficult for conventional conditioning agents to achieve effective dehydration.

[0250] Experimental sample setup

[0251] Example 4: The conditioning agent consists of sodium metamolybdate (Na2MoO4), sodium persulfate, sulfobetaine and nano titanium dioxide.

[0252] Comparative Example 4: The conditioner does not contain the nanoparticle auxiliary agent.

[0253] Comparative Example 5: The concentration of the Lewis acid metal salt was halved (compared with Example 4).

[0254] Experimental steps:

[0255] Adding conditioning agent: Add the corresponding conditioning agent to the sludge at a ratio of 8‰ of the wet mass of the sludge;

[0256] Stirring reaction: Use low-speed stirring equipment to stir, the speed is set to 60rpm, and the stirring time is 3 minutes to ensure that the conditioner is in full contact with the sludge;

[0257] Standing reaction: After standing for 10 minutes, observe the oil-water separation phenomenon and record the oil droplet precipitation;

[0258] Mechanical dehydration: send the conditioned sludge into the centrifugal dehydrator at a speed of 2000rpm. Record the moisture content of the sludge after dehydration;

[0259] Determination of oil content in filtrate: Collect the dehydrated filtrate and use a fat analyzer to determine the oil content (mg / L) in the filtrate to characterize the oil-water separation effect.

[0260] Experimental data recording

[0261] Each experiment was repeated three times, and the moisture content of the sludge after dehydration and the oil content of the filtrate were recorded.

[0262] Experimental data table

[0263] Table 4: Experimental data of the effects of different conditioners on the dehydration of high oil content sludge:

[0264]

[0265] Experimental summary:

[0266] Example 4 shows an outstanding effect in treating high-oil sludge. The nanoparticle additive plays a core role in this. Nano-titanium dioxide provides a large number of active sites, which not only strengthens the effect of the conditioner on the surface of the sludge particles, but also forms a stable microstructure barrier, effectively inhibiting the recombination of oil molecules and water molecules. In comparative example 4, although the destabilization and aggregation between sludge particles still exist, the loose particle structure leads to a significant decrease in the oil-water separation efficiency, and the oil content in the filtrate is high. This shows the criticality of nanoparticles for the dehydration of high-oil sludge.

[0267] For Comparative Example 5, the reduced concentration of Lewis acid metal salt makes it perform better than Comparative Example 4, but still inferior to Example 4. This phenomenon clearly shows that the Lewis acid metal salt changes the chemical properties of the surface of the sludge particles through coordination, destroying the binding force between the oil and grease and the sludge particles. After reducing the Lewis acid concentration, the effect of this modification is weakened, and the destabilization degree of the particles is also affected, which is manifested in the high oil content of the filtrate and the unsatisfactory water content of the sludge after dehydration.

[0268] The role of free radical generators cannot be ignored. In Example 4, sulfate radicals degraded the organic protective layer on the surface of the sludge particles through strong oxidation, providing more room for the role of Lewis acid and surfactant. In Comparative Example 5, although the free radical generator still exists, the synergy of the entire conditioning process is weakened due to insufficient Lewis acid concentration. This imbalance is directly reflected in the dehydration efficiency and the oil content of the filtrate. Compared with Example 4, the moisture content of the dehydrated sludge is slightly higher, and the oil content of the filtrate is also higher. Combined with the above observations, the overall technical solution of Example 4 can better meet the treatment needs of high-oil sludge.

[0269] Experiment 5: Effect of conditioning agent dosage on sludge dewatering efficiency

[0270] Subjects:

[0271] This experiment uses municipal sludge with an initial moisture content of 78% and a total sludge mass of 100 kg. The sludge comes from the primary sedimentation tank of the municipal sewage treatment plant. This type of sludge has fine particles and high content of bound water and colloidal water. The dehydration efficiency is closely related to the amount of conditioning agent used.

[0272] Experimental sample setup:

[0273] Example 1: The composite conditioner was used to treat sludge at dosages of 5‰, 7‰ and 10‰ respectively.

[0274] Comparative Example 1: The conditioning agent does not contain Lewis acid metal salt, and the dosage is fixed at 7‰.

[0275] Experimental steps:

[0276] Conditioner addition: Add each group of conditioners to 100kg of municipal sludge according to the designed proportion to ensure that the dosage and formula of different groups are consistent;

[0277] Stirring reaction: Use a stirring device to stir at 60 rpm for 3 minutes to evenly disperse the conditioning agent;

[0278] Standing reaction: After standing for 10 minutes, observe the separation of sludge particles and the state of liquid phase precipitation;

[0279] Mechanical dehydration: The conditioned sludge sample is sent to the belt filter press, and the operating pressure is set to 0.4MPa. The moisture content of the sludge after dehydration is recorded, and the filtration time is measured.

[0280] Experimental data record:

[0281] The moisture content and filtration time of each group of sludge after dehydration were recorded. The experiment was repeated 3 times and the average value was taken.

[0282] Experimental data table:

[0283] Table 5: Experimental data on the effect of conditioning agent dosage on sludge dewatering:

[0284]

[0285] Experimental summary:

[0286] The amount of conditioning agent directly affects the sludge dewatering effect. In Example 1, the moisture content and filter pressing time under different dosages show regularity. When the dosage is 5‰, the moisture content of the sludge after dehydration is 47.8%, and the filter pressing time is relatively long. As the dosage increases to 7‰, the moisture content drops to 42.5%, and the filter pressing time is shortened to 18.7 minutes. When it is further increased to 10‰, the sludge moisture content is further reduced to 40.2%, but the effect improvement tends to be flat. This shows that the higher the dosage of the conditioning agent within a certain range, the better the efficiency of releasing bound water, but after exceeding the optimal dosage, the synergistic effect of the conditioning agent gradually weakens, resulting in a decrease in economic efficiency.

[0287] The dehydration effect of Comparative Example 1 is obviously inferior to that of Example 1, which fully demonstrates the important role of Lewis acid metal salt. Lewis acid destroys the polar groups on the surface of sludge particles through coordination, thereby releasing strongly bound water. In Comparative Example 1, due to the lack of Lewis acid metal salt, the surface structure of the sludge particles remains intact, and the removal efficiency of bound water is greatly reduced. The increase in the amount of conditioning agent has limited improvement on the effect of Comparative Example 1, indicating that it is difficult to achieve a significant improvement in dehydration efficiency by relying solely on the effects of flocculation and surfactants.

[0288] From a mechanistic point of view, the synergistic effect of free radical generators and nano-additives is particularly evident in high-dosage conditioners. The free radicals generated by persulfate reduce the chemical stability of the surface of sludge particles through oxidation, while nano zinc oxide provides more reaction sites and enhances the agglomeration effect between particles. At a higher dosage (10‰), this synergistic effect makes the particle structure more stable and significantly reduces the resistance to mechanical dehydration. Therefore, Example 1 achieves excellent dehydration effect under appropriate dosage conditions, while Comparative Example 1 lacks a core modified component, which makes it difficult to significantly improve its dehydration efficiency. Combined with the experimental results, the optimal dosage of the conditioner is recommended to be 7‰, which can achieve the effect of efficient dehydration and has good economy.

[0289] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A composite conditioner for sludge dehydration, characterized in that: Includes the following components: Lewis acid metal salts; Free radical generators; Surfactants; Polymeric flocculants; Nanoparticle additives; pH adjuster.

2. A sludge dehydration composite conditioner according to claim 1, characterized in that: The Lewis acid metal salt is a titanate or a vanadate, specifically at least one of titanium tetrachloride, sodium metavanadate, and sodium metamolybdate.

3. A sludge dehydration composite conditioner according to claim 1, characterized in that: The free radical generator is a persulfate, specifically at least one of sodium persulfate and ammonium persulfate.

4. A sludge dehydration composite conditioner according to claim 1, characterized in that: The surfactant is an amphoteric surfactant, specifically sulfobetaine or alkylbetaine.

5. The sludge dehydration composite conditioner according to claim 1, characterized in that: The polymeric flocculant is cationic polyacrylamide.

6. A sludge dehydration composite conditioner according to claim 1, characterized in that: The nanoparticle auxiliary agent is zinc oxide or titanium dioxide nanoparticles, and the particle size thereof is 10nm to 100nm.

7. The sludge dehydration composite conditioner according to claim 1, characterized in that: The pH regulator is sodium hydroxide or sodium carbonate.

8. A method for preparing a composite conditioner for sludge dehydration, characterized in that: A sludge dehydration composite conditioner applied to any one of claims 1 to 7, comprising the following steps: Dissolving a Lewis acid metal salt in deionized water and adjusting the pH to obtain a Lewis acid active solution; dissolving a free radical generator in deionized water to obtain a free radical solution; Dissolving a surfactant in deionized water to prepare a surfactant solution; dispersing the nanoparticle auxiliary agent in deionized water by ultrasonication to obtain a nanoparticle auxiliary agent suspension; The Lewis acid active liquid, the free radical solution, the surfactant solution, the nanoparticle auxiliary agent suspension and the flocculant are sequentially mixed according to proportions and stirred evenly to prepare a sludge dehydration composite conditioner.

9. The method for preparing a composite sludge dehydration conditioner according to claim 8, characterized in that: The dissolution concentration of the Lewis acid metal salt is 20% to 40%, and the pH adjustment range is 6.5 to 7.

5.

10. The method for preparing a composite sludge dehydration conditioner according to claim 8, characterized in that: The power of the nanoparticle auxiliary agent dispersed by ultrasound is 100W to 200W, the frequency is 20kHz to 40kHz, and the ultrasound time is 10 minutes to 20 minutes.

Citation Information

Patent Citations

  • Sludge deep dehydration composite conditioner and its application

    CN103819072A

  • High-efficiency sludge dehydrating agent

    CN107746171A

  • Chemical conditioning deep dehydration method for sludge

    CN114804570A

  • Nano highly effective amendment for sludge dehydration

    CN1621370A

  • Powdery organic coagulant

    JP2014184406A

Cited By

  • Fracturing flow-back fluid treatment agent and fracturing flow-back fluid treatment process

    CN121107626A